Effects of intense rainfall on stability of infinite terraced slope - Ma, Shi-guo; Han, Tong-chun; Xu, Ri-qing; Wu, Jian; Zhang, Jie (Journal of Central South University, 2014)
For fully understanding the hydrological dynamics of an infinite terraced slope, the infiltration process was studied by employing the Green and Ampt infiltration model. The limit equilibrium method and the Mohr-Coulomb failure criterion were adopted to derive a stability model for the infinite terraced slope subjected to an intense rainfall. Numerical simulation was performed for verifying its applicability. The results of numerical simulation indicate that a set of stepped wetting fronts are found during infiltration, and the infiltration of terraced slope covered by coarse-textured soils can be approximated as one-dimensional infiltration. The potential sliding surfaces from the numerical method are all parallel to the slope line, and the proposed model and framework can provide an approximate method of estimating how the infiltration affects the stability of an infinite terraced slope.